Asymptotics and Consistent Bootstraps for DEA Estimators in Non-parametric Frontier Models - Alois Kneip; Léopold Simar; Paul W. Wilson (University of Bonn, Bonn Graduate School of Economics (BGSE), 2006)
Non-parametric data envelopment analysis (DEA) estimators based on linear programming methods have been widely applied in analyses of productive efficiency. The distributions of these estimators remain unknown except in the simple case of one input and one output, and previous bootstrap methods proposed for inference have not been proven consistent, making inference doubtful. This paper derives the asymptotic distribution of DEA estimators under variable returns-to-scale. This result is then used to prove that two different bootstrap procedures (one based on sub-sampling, the other based on smoothing) provide consistent inference. The smooth bootstrap requires smoothing the irregularly-bounded density of inputs and outputs as well as smoothing of the DEA frontier estimate. Both bootstrap procedures allow for dependence of the inefficiency process on output levels and the mix of inputs in the case of input-oriented measures, or on inputs levels and the mix of outputs in the case of output-oriented measures.
Keywords: C12; C14; C15; 330; bootstrap; frontier; efficiency; data envelopment analysis; DEA